Reactive oxygen species (ROS) and response of antioxidants as ROS-scavengers in contrasting rice (Oryza sativa L.) genotypes under drought stress - Parida, Selukash; Dash, Goutam Kumar; Samal, Kailash Chandra; Swain, Padmini (ORYZA-An International Journal of Rice, 2022)
The role of antioxidative enzymes as reactive oxygen species-scavengers under water-limited (WL) conditions was studied in five contrasting rice genotypes, including two checks (Sahabhagidhan as a tolerant genotype and IR 64 as a susceptible genotype). The experiment was performed in pots, and the irrigation was withdrawn five days before flowering for 15 days. For stress imposition, stress pots were maintained at 50% field capacity whereas nonstress pots were maintained at 100% field capacity. The antioxidant enzyme activity such as superoxide dismutase (SOD), catalase (CAT), and peroxidase (POX), was significantly increased under the WL conditions. Genotypes Sahabhagidhan and Parijata had the highest SOD, CAT, and POX activity with the lowest production of superoxide radical (O2-) and hydrogen peroxide (H2O2). At the same time, IR 64 and Prasad exhibited the lowest SOD, CAT, and POX activity, suggesting a lower potential to eliminate oxidative stress. The higher scavenging capacity of free radicals in Sahabhagidhan and Parijata was supplemented by the higher level of relative water content (RWC), membrane stability index (MSI), Maximum quantum yield of PSII photochemistry (Fv/Fm), chlorophyll content, and low lipid peroxidation which resulted in higher grain yield accompanied by higher biomass partitioning towards the grain.